2020
DOI: 10.1038/s41598-020-61252-3
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Perception of Biological Motion in Autism: A Conceptual Review and Meta-Analysis

Abstract: Despite its popularity, the construct of biological motion (BM) and its putative anomalies in autism spectrum disorder (ASD) are not completely clarified. In this article, we present a meta-analysis investigating the putative anomalies of BM perception in ASD. Through a systematic literature search, we found 30 studies that investigated BM perception in both ASD and typical developing peers by using point-light display stimuli. A general meta-analysis including all these studies showed a moderate deficit of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 160 publications
5
57
2
1
Order By: Relevance
“…We performed a post hoc power analysis to check whether this sample size was acceptable for the 3 × 2 × 3 mixed ANCOVA model to detect an effect. We ran a post hoc F-test power analysis (R package pwr) with medium effect size of 0.15 and sample size equal to 69 (see estimated effect size from Federici et al, 2019). We obtained that the power of detecting such an effect at 0.05 level is equal to 0.90.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a post hoc power analysis to check whether this sample size was acceptable for the 3 × 2 × 3 mixed ANCOVA model to detect an effect. We ran a post hoc F-test power analysis (R package pwr) with medium effect size of 0.15 and sample size equal to 69 (see estimated effect size from Federici et al, 2019). We obtained that the power of detecting such an effect at 0.05 level is equal to 0.90.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many reports of reduced sensitivity to biological motion in individuals with ASD [ 68 70 ], there are likewise a number of reported null findings [ 71 73 ]. Recent meta-analyses aimed at clarifying these discrepancies concluded that biological motion effects in ASD are weak, non-specific, and highly conditional on experimental design [ 45 , 46 , 74 ]. Experimental design may vary with respect to task features (e.g., spatially scrambled vs. phase-scrambled motion [ 68 , 70 ]), sample characteristics (e.g., infants vs. adults [ 75 , 76 ]), and response set (e.g., preferential looking vs. reaction time [ 76 , 77 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of researches is closer to our approach, given that it focuses young people as a subject; in this sense, it is mainly a domain of psychology, rather than sociology. This means that often the attention of the researchers concentrates better on deviance aspects instead of ordinary ones; phenomena like hikikomori 2 and addictions of various kinds are widely studied (for example Takahiro & Kato, 2019) as well as some acknowledged actual behavioural pathologies like autism (Federici et al , 2020 ;Gallese & Rochat, 2018;Gallese et al , 2012 ;Zappella, 2005;Frith, 1989Frith, -2009 or borderline behaviours like ADHD (Attention-Deficit / Hyperactivity Disorder) and SLD (Specific Learning Disabilities, like dyslexia and others) in young people, also with highly specialistic studies. For example about ADHD, what is it and how to treat: American Psychiatric Association, 2013; Steinau, 2013;Rigoni et al , 2020 ;Danielson et al , 2018.…”
Section: Introductionmentioning
confidence: 99%